Exacerbation of alopecia areata: A possible complication of sodium tetradecyl sulphate foam sclerotherapy treatment for varicose veins - Whiteley, Mark S (SAGE Open Med Case Rep, 2017)
A 40-year-old woman with a history of alopecia areata related to stress or hormonal changes was treated for bilateral primary symptomatic varicose veins (CEAP clinical score C2S) of pelvic origin, using a staged procedure. Her first procedure entailed pelvic vein embolisation of three pelvic veins using 14 coils and including foam sclerotherapy of the tributaries, using 3% sodium tetradecyl sulphate. Following this procedure, she had an exacerbation of alopecia areata with some moderate shedding of hair. Subsequently, she underwent endovenous laser ablation under local anaesthetic without incident. Seven months after the pelvic vein embolisation, she underwent foam sclerotherapy of leg and labial varicose veins using sodium tetradecyl sulphate. Two days following this procedure, she had a severe exacerbation of alopecia areata with gross shedding of hair. These two episodes of exacerbation of alopecia areata appear to be associated with sodium tetradecyl sulphate foam sclerotherapy of veins.